STUDY OF TECHNOLOGICAL PARAMETERS AND PHYSICAL-MECHANICAL PROPERTIES OF RIB FABRIC KNITTED FROM SPINNING COTTON-NITRON YARN - Karimov, Nuriddin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
For the purpose of effective use of local cotton-nitron yarn in the scientific work was conducted on the technological indicators and physical mechanical properties of rib stitch fabric.